First record of Ektaphelenchoides pini associated with Ips sexdentatus on Pinus nigra laricio in Italy. Issue 4 (29th July 2020) - d'Errico, Giada; Fanelli, Elena; Troccoli, Alberto; Binazzi, Francesco; Landi, Silvia; Roversi, Pio; De Luca, Francesca
Abstract: In February 2015, an unexpected windstorm downed five hectares of a European black pine Pinus nigra subsp. l aricio forest formation located close to Vallombrosa, Florence (Central Italy). In the following spring, an extensive survey was conducted in the area. Felled trees, stumps and all the suitable plant material were screened for the presence of the pinewood nematode (PWN), Bursaphelenchus xylophilus, by sampling wood and bark. Bark beetles were then collected from the gallery systems on the inner side of bark samples and observed in the laboratory. The following bark beetles were morphologically identified: Ips sexdentatus, Orthotomicus erosus, O. laricis and Pityogenes bidentatusa . The dissection of Ips sexdentatus allowed the extraction of numerous nematodes that were morphologically and molecularly identified as Ektaphelenchoides pini . Conversely, only few nematode specimens were isolated from either pine bark or wood. These individuals could be only molecularly identified and belonged to an undescribed nematode taxon. Even though no PWN was recorded in the investigated sites, our survey allowed the detection of a new association between E. pini and I. sexdentatus on P. nigra .